An exploration of the variability of physiological responses to soil drying in relation with C/N balance across three species of the under‐utilized genus Vigna. Issue 2 (4th November 2020) - Guiguitant, Julie; Marrou, Hélène; Vile, Denis; Sinclair, Thomas R.; Pradhan, Deepti; Ramirez, Martha; Ghanem, Michel Edmond
Abstract: The genus Vigna (Fabaceae) is an agriculturally important taxon, which includes several crop species such as cowpea ( Vigna unguiculata L.), mung bean ( Vigna radiata ) and azuki bean ( Vigna angularis ). Most studies have focused on cowpea ( V. unguiculata (L.) as a drought‐resistant crop, although insights on the mechanisms that confer this species the ability to grow in dry environment are still not fully resolved. The diversity of this rich genus has been overlooked in many physiological studies. This study explores the physiological mechanisms of response to soil drying (N2 fixation, transpiration rate and changes in C and N allocation) across three species of the Vigna genus: V. radiata, V. unguiculata, V. vexillata (tuber cowpea). A significant variability among the studied Vigna accessions was found for the threshold in decline of N2 fixation with soil drying. Less variability was observed in the transpiration threshold. Through the analysis of leaf traits variation under well‐watered and water‐deficit conditions, we were able to relate the variability in N2 fixation and transpiration response to C/N metabolism modifications resulting in different allocation of carbon and nitrogen to leaves under water deficit.